Beliefs of Chilean University English Teachers: Uncovering Their Role in the Teaching and Learning Process - Díaz Larenas Claudio; Alarcón Hernández Paola; Vásquez Neira Andrea; Pradel Suárez Boris; Ortiz Navarrete Mabel (Universidad Nacional de Colombia, 2013)
<span style="font-size: 10.0pt; font-family: ";Verdana";,";sans-serif";; mso-fareast-font-family: ";Times New Roman";; mso-fareast-theme-font: minor-fareast; mso-bidi-font-family: ";Times New Roman";; mso-ansi-language: EN-US; mso-fareast-language: ES-CO; mso-bidi-language: AR-SA;" lang="EN-US">Beliefs continue to be an important source to get to know teachers' thinking processes and pedagogical decisions. Research in teachers' beliefs has traditionally come from English-speaking contexts; however, a great deal of scientific work has been written lately in Brazil, Mexico, Colombia, and Argentina. This study elicits 30 Chilean university teachers' beliefs about their own role in the teaching and learning of English in university environments. Through a qualitative research design, the data collected from interviews and journals were analyzed, triangulated, and categorized based on semantic content analysis. Results of the study indicate that university teachers reveal challenging and complex views about what it is like to teach English as a foreign language in a university context in Chile. The article concludes with a call to reflect on the importance of beliefs unravelling in teacher education programmes. <span style="font-size: 10.0pt; font-family: ";Verdana";,";sans-serif";; mso-fareast-font-family: ";Times New Roman";; mso-fareast-theme-font: minor-fareast; mso-bidi-font-family: ";Times New Roman";; mso-ansi-language: ES-CO; mso-fareast-language: ES-CO; mso-bidi-language: AR-SA;">Las creencias continúan siendo una fuente de importancia para conocer los procesos de pensamiento y los estilos pedagógicos de los docentes. Los estudios sobre las creencias docentes provienen en su mayoría de contextos angloparlantes; sin embargo, en los últimos años se ha escrito una gran cantidad de trabajos científicos en Brasil, México, Colombia y Argentina. Este estudio recoge las creencias de treinta docentes universitarios chilenos sobre su papel en la enseñanza y aprendizaje del inglés en ambientes universitarios. A partir de un diseño de investigación cualitativo, los datos recolectados por medio de entrevistas y diarios personales fueron analizados, triangulados y categorizados según el análisis de contenido semántico. Los resultados indicaron que los docentes de educación superior tienen visiones desafiantes y complejas sobre lo que significa enseñar inglés como lengua extranjera en un contexto universitario en Chile. El artículo concluye con una invitación a reflexionar sobre la importancia de transparentar las creencias en los programas de formación inicial docente.